Edo Japan encounters the world - Keene, Donald (Japan Publishing Industry Foundation for Culture, 2018)
Edo Japan Encounters the World continues the conversation, begun nearly twenty years earlier in The People and Culture of Japan, between scholar of Japanese literature Donald Keene and historical novelist Shiba Ryotaro. In discussions that took place in Osaka and Kyoto from 1989 to 1990, these two penetrating and original observers of Japanese culture turn their attention to the long peace of the Edo period (1603-1868), when Japan developed in relative isolation from outside influence. From analysis of literary masters like Basho and Chikamatsu to critiques of the repressive aspects of Edo life, their exchanges bring much insight to this often romanticized period of Japanese history.